2016
DOI: 10.1038/jhh.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns, nutrition knowledge and lifestyle: associations with blood pressure in a sample of Australian adults (the Food BP study)

Abstract: This study examined the association between dietary patterns, nutrition knowledge and lifestyle with blood pressure (BP) in a sample of Australian adults. Adults with normal and high BP were included in a cross-sectional study. Dietary intake data was collected using a Food Frequency Questionnaire. Nutrition knowledge and lifestyle surveys were included in the questionnaire. Dietary patterns were extracted using factor analysis followed by cluster analysis. Associations were analysed using logistic regression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…Survey data were collected between May and September 2017 at CQU and between February and June 2018 at Griffith University using SurveyMonkey (http://www.surveymonkey.com). Food and dietary habits were measured using a food frequency questionnaire (FFQ) (59 items), previously developed and validated in an Australian population by the project leader (Irwin, Khalesi, Fenning, & Vella, ; Khalesi, Sharma, Irwin, & Sun, ). Participants were asked to report their food consumption frequency in the past 12 months in daily, weekly, or monthly format using a 10 point scale (from “never” to “3–5 times per day”).…”
Section: Methodsmentioning
confidence: 99%
“…Survey data were collected between May and September 2017 at CQU and between February and June 2018 at Griffith University using SurveyMonkey (http://www.surveymonkey.com). Food and dietary habits were measured using a food frequency questionnaire (FFQ) (59 items), previously developed and validated in an Australian population by the project leader (Irwin, Khalesi, Fenning, & Vella, ; Khalesi, Sharma, Irwin, & Sun, ). Participants were asked to report their food consumption frequency in the past 12 months in daily, weekly, or monthly format using a 10 point scale (from “never” to “3–5 times per day”).…”
Section: Methodsmentioning
confidence: 99%
“…A resting blood pressure recording was then taken using an automatic blood pressure monitor (Omron HEM-7203, Omron HealthCare Co. Ltd., Kyoto, Japan) and immediately after, a 10 mL blood sample was collected from the antecubital forearm vein, using standard phlebotomy procedures. Participants were then asked to complete a food frequency questionnaire (FFQ) 8 [34,35], which indicated dietary consumption patterns over the previous 4 weeks. The FFQ was modified to also contain a detailed section for evaluating consumption of prebiotic and probiotic foods and fluids.…”
Section: Experimental Trial Proceduresmentioning
confidence: 99%
“…Thus with less variation in dietary intake, there may be less ability to detect associations with BP. Although our sample size was less than 300 individuals, this is comparable to other analyses assessing associations between dietary patterns and other markers of chronic disease [24,25,36,55,56]. A key strength of this study is the use of home BP measurements which have been shown to share the many advantages of ambulatory monitoring.…”
Section: Discussionmentioning
confidence: 73%
“…Dietary patterns also differ among certain populations within a country depending on factors such as age, sex and education level [22,23]. To date there has been little published research on the association between dietary patterns and BP in Australian adults [24,25]. A study by Livingstone et al, using data from two 24-h recalls on 4908 adults from the Australia National Nutrition and Physical Activity Survey, found a dietary pattern, determined by reduced rank regression, characterised by low fibre density and high sodium to potassium ratio (Na:K) and high saturated fat to polyunsaturated fat ratio, was associated with a higher prevalence of hypertension [26].…”
Section: Introductionmentioning
confidence: 99%